Studi Kasus Asuhan Kehamilan Pada Ny. A Di UPT Puskesmas Sooko Kab. Mojokerto - Dhonna Anggreni; Titania Hernanda Munita Putri (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2021)
One indicator to see the success of maternal health is by monitoring the Maternal Mortality Rate (MMR). In Mojokerto Regency, the MMR in 2019 was 89.60 per 100,000 live births. Reducing mortality and improving the quality of maternal and child health will achieve the expected results if accompanied by an increase in antenatal care and delivery assistance by health workers. The purpose of this study was to provide obstetric care for pregnant women. This type of research is a case study by providing obstetric care for pregnant women. This research was conducted using midwifery management and documentation using SOAP. The sample in this study was 1 respondent. The research was conducted at UPT Puskesmas Sooko, Mojokerto Regency. By holding this activity, it is hoped that maternal health during pregnancy can be maintained and be able to produce a healthy and intelligent generation